2014
DOI: 10.1186/1756-3305-7-211
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal effect of disinfectant soap on Anopheles gambiae s.s (Diptera: Culicidae) in laboratory and semifield environs

Abstract: BackgroundMosquito larval control using chemicals and biological agents is of paramount importance in vector population and disease incidence reduction. A commercial synthetic disinfectant soap was evaluated against larvae of Anopheles gambiae s.s. in both laboratory and semi field conditions.MethodFive concentrations of commercial synthetic disinfectant soap (0.0001, 0.001, 0.01, 0.1 and 1%) were prepared and evaluated against third instar larvae in laboratory and semi field environments. Mortality was scored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…In this study, the studied oils (JVO, PRO, and PRO main components) showed anti-mosquito (larvicidal and adulticidal) activities under different conditions. The larval mortality rates were higher in laboratory environment than semi-field conditions, as reported by other studies [45,46,49,50]. The trend of LC 50 values of JVO larvicidal activity raised with increasing exposure time, which is in line with other investigations [51,52].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the studied oils (JVO, PRO, and PRO main components) showed anti-mosquito (larvicidal and adulticidal) activities under different conditions. The larval mortality rates were higher in laboratory environment than semi-field conditions, as reported by other studies [45,46,49,50]. The trend of LC 50 values of JVO larvicidal activity raised with increasing exposure time, which is in line with other investigations [51,52].…”
Section: Discussionsupporting
confidence: 90%
“…The dead and moribund larvae were both considered dead. Experiments were set in both laboratory and semi-field conditions as described elsewhere [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…gambiae complex to chemical insecticides permethrin, deltamethrin and neonicotinoids. [14][15][16] Thus, in addition to the development of insecticide resistance being a major limiting step in malaria elimination in Africa, the environment in which mosquitoes inhabit is quickly becoming an important factor to consider with regard to vector control.…”
Section: Introductionmentioning
confidence: 99%